Pengaruh Pertimbangan Masyarakat dalam Pemilihan Sambungan pada Konstruksi Bangunan Bambu - Pratiwi, Dian; Ivada, Nursella; Larasati, Dewi (Department of Architecture, Faculty of Science and Technology, Alauddin State Islamic University, 2025)
The utilization of bamboo as a construction material remains infrequent, despite its widespread availability in Indonesia as a natural resource. This reluctance can be attributed to prevailing perceptions of its low durability, deeming it suitable only for temporary structures. Contrary to such notions, bamboo stands as a sustainable biomass material, offering potential solutions to alleviate the environmental impact associated with conventional construction practices. Nevertheless, the incorporation of bamboo in the construction sector, particularly in joint applications, poses notable challenges. This research endeavors to discern the factors influencing individuals' preferences in selecting various types of bamboo connections. Research methods using a qualitative approach from literature and questionnaires. Data analysis involves distribution and correspondence analysis. The findings reveal that internal considerations, encompassing ease of application, connection strength alignment with construction requirements, aesthetics, durability, and material cost, significantly shape the choice of connection types. Furthermore, external factors, specifically the influence of consultants and the expertise of craftsmen, play a pivotal role in the decision-making process. An efficient jointing system typically prioritizes factors such as strength, durability and cost. However, in this context of bamboo jointing systems, additional considerations - such as ease of application, the availability of materials, and aesthetic quality should also be taken into account. This research aspires to enhance understanding regarding the criteria guiding the selection of bamboo connections among the populace, thereby fostering a broader integration of bamboo within the construction industri in a manner that is both sustainable and environmentally conscientious.